1462. The protective effect of pneumococcal vaccination on cardiovascular disease in adults: A systematic review and meta-analysis - Marra, Fawziah (Open Forum Infect Dis, 2020)
BACKGROUND: Epidemiological studies suggest a link between pneumococcal infection and an adverse cardiovascular outcome such as myocardial infarction. Therefore, studies have evaluated the protective effect of the 23-valent polysaccharide pneumococcal vaccination (PPV23), but results have varied. We conducted a meta-analysis to summarize the available evidence on the impact of PPV23 on cardiovascular disease METHODS: A literature search from January 1946 to September 2019 was conducted in Embase, Medline and Cochrane. All studies evaluating PPV23 compared to a control (placebo, no vaccine or another vaccine) for any cardiovascular events including myocardial infarction (MI), heart failure, cerebrovascular events were included. Risk ratios (RRs) were pooled using random effects models. RESULTS: Eighteen studies were included, with a total of 716,108 participants. Vaccination with PPV23 was associated with decreased risk of any cardiovascular event (RR: 0.91;95% CI: 0.84-0.99), and MI (RR of 0.88; 95% CI:0.79-0.98) in all age groups, with a significant effect in those 65 years and older, but not in the younger age group. Similarly, PPV23 vaccine was associated with significant risk reduction in all-cause mortality in all ages (RR: 0.78; 95%CI: 0.68-0.88), specifically in those aged 65 years and older (RR: 0.71; 95%CI: 0.60-0.84). A significant risk reduction in cerebrovascular disease was not observed following pneumococcal vaccination. CONCLUSION: Polysaccharide pneumococcal vaccination decreases the risk of a cardiovascular event, specifically acute MI in the vaccinated population, particularly those 65 years of age and older. It would be highly beneficial to vaccinate the population who is at greater risk for cardiovascular diseases. DISCLOSURES: Fawziah Marra, BSc (Pharm), PharmD, Pfizer Inc (Research Grant or Support) Nirma Khatri Vadlamudi, BA, BS, MPH, Pfizer Inc (Research Grant or Support)